2014 IEEE/ACS 11th International Conference on Computer Systems and Applications (AICCSA) 2014
DOI: 10.1109/aiccsa.2014.7073266
|View full text |Cite
|
Sign up to set email alerts
|

HLS based hardware acceleration on the zynq SoC: A case study for fall detection system

Abstract: Fall detection is a major problem in healthcare systems, especially for elderly people who are the most vulnerable. It is important to design and implement not only an accurate fall detection system (FDS) but also a system with a real-time response. The achievement of high accuracy and fast response time together allows the development of a system that helps saving lives, time and money in healthcare industry. This paper presents the design, simulation and implementation of a novel FDS using the Shimmer wearab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The recorded triaxial accelerometer signal consisted of a 3-dimensional vector, with each component corresponding to each of the three axes/dimensions x , y , z respectively. An analysis of the captured signals showed that the duration of an event that caused acceleration was not longer than 2 s, as also pointed out in [ 26 ]. Using the information from the captured videos from each experiment and the corresponding video and accelerometer timestamps, the acquired signals were first divided into segments that contained only one event each.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…The recorded triaxial accelerometer signal consisted of a 3-dimensional vector, with each component corresponding to each of the three axes/dimensions x , y , z respectively. An analysis of the captured signals showed that the duration of an event that caused acceleration was not longer than 2 s, as also pointed out in [ 26 ]. Using the information from the captured videos from each experiment and the corresponding video and accelerometer timestamps, the acquired signals were first divided into segments that contained only one event each.…”
Section: Methodsmentioning
confidence: 58%
“…Ali et al [ 26 ] proposed a fall detection system based on a system-on-chip (SoC) board that utilised a triaxial accelerometer for real-time fall detection. The Discrete Wavelet Transform (DWT) and PCA were used for feature extraction and fall detection accuracy reached 88.4% using a Decision Tree classifier.…”
Section: Introductionmentioning
confidence: 99%
“…The processing of entire window segment with arithmetic trees results in a higher throughput and an effective latency of 0.1 µs/sample with 128 sample bursts of data streaming into the proposed hardware design. The latest works in [66,67] have a higher latency of 1 s, while [47,50,51] have latencies in microseconds, however they suffer form lower classification performance. Furthermore, the proposed system also consumes relatively low to moderate resources over all hardware implementations from design I to final design, which allows flexibility in performance and area trade-off requirements for processing.…”
Section: Hardware System Resultsmentioning
confidence: 99%
“…However, their implementation did not give any power consumption values. Ali et al [47] implemented a sensor-based FDS on a Zynq System on Chip (SoC) device which applies DWT and PCA for feature extraction and a binary decision tree for classification. The system suffered from lower accuracy and no power consumption analysis has been performed.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [48] present the design, simulation and implementation of a novel fall detection system based on the Shimmer platform and Zynq board. In this prototype, accelerometer data are sent to the processing unit by Bluetooth.…”
Section: Advantages Of Fpgas In Fall Detection Systemsmentioning
confidence: 99%